Analisis Faktor Penyebab Perilaku Merokok - Ida Suryawati; Abdul Gani (Jurnal Keperawatan Silampari, 2022)
This study aims to investigate what are the reasons for smoking behavior. The research design used is qualitative with a descriptive phenomenological approach. Based on the results obtained in this study, six themes: are perceptions about smoking, knowledge, curiosity, peers, work, and family. Simply put, smoking behavior in adolescents continues to increase every year. This increase occurs because many things can influence smoking behavior, including social and environmental factors, characteristic psychological factors, and lifestyle factors, while the family environment also influences smoking behavior. Keywords: Willing, Behaving